CE conformity markin - Tricker, Ray. (Boston : Butterworth-Heinemann, 2000)
CE Marking can be regarded as a product's trade passport for Europe. It is a mandatory European marking for certain product groups to indicate conformity with the essential health and safety requirements set out in the European Directive. The prime aim of the CE Directive is to ensure that "all industrial products that are placed on the market do not compromise the safety and health of users when properly installed, maintained and used in accordance with their intended purpose. Users and third parties should be provided with a high level of protection and the devices should attain the performance levels claimed by the manufacturer." This book explains the meaning of CE Marking, its history, how the Directive can affect all manufacturers of industrial products, its current status, its associated quality management requirements, and how manufacturers can easily and cost-effectively meet the requirements for CE Conformance. Essential information for any manufacturer or distributor wishing to trade in the European Union. Practical and easy to understand.
1. BACKGROUND TO THE NEW APPROACH DIRECTIVES: European Directives; Transition Period and Overlapping of Directives; Application; Mutual Recognition Agreements/European Conformity Assessment Protocols; Types of Directives and Standards; Concurrent Application of Directives; Aim of Standardisation; International Standardisation; Harmonised European Standards; Revision of Harmonised Directives; Management of the List of Standards; Recognition of European Standards. 2. STRUCTURE OF NEW APPROACH DIRECTIVES: Articles; Adoption of New Approach Directives; Transposition of New Approach Directives; Advisory Committee; Review and Reporting; Transitional Provisions; Repeal; Entry into Force. 3. STRUCTURE OF THE CE CONFORMITY MARKING DIRECTIVE (93/465/EEC): Main Part; General Guidelines; Conformity Assessment Modules -- Short Description; Choice of Module; CE Marking; Industrial Product Type conformity; Competent Authority; Notified Bodies; Essential Standards for Notified Bodies; Relevant Standards of the EN45000 Series for Each Module; Notified Bodies Tasks Under Each Module; Requirements of the Various Directives affected by CE Marking; Content of the Directives; Conformance; Principle Directives; Other Directives; Medical Devices -- in vitro diagnostics (COM (95) 130) 180; Other Directives Associated with the CE Marking Directive. -- 4. GAINING OF CONFORMITY: Self Declaration; Voluntary Certification; Mandatory Certification; The 5 Steps to Conformity; Quality Management System; Conformity Assessment Procedures; Conformity requirements of each Module; Conformance Requirements of New Approach Directives; Manufacturers; Manufactuer's Tasks Under Each Module; Basic Requirements of manufacturers of Industrial Products; Registration of manufacturers; EC Verification; Design and Construction Requirements; Index.
Includes index.
Keywords: Quality assurance -- European Union countries; Standardization -- European Union countries -- Marks; Quality control -- Standards -- European Union countries; ISO 9000 Series Standards; Product safety -- Standards -- European Union countries; Europe -- European Union countries; Electronic books